Systematic Approach in Designing a Novel Hydrogen-based Integrated Hybrid Renewable Energy System with a Small-scale Combined Cycle Plant - Tuck Kong Lok; Jeng Shiun Lim (Chemical Engineering Transactions, 2023)
The energy transition stage is experiencing significant growth in renewables, waste-to-energy, and hydrogen-based systems for electricity generation. Energy storage is being recognized as a crucial solution to enable these penetrations especially with recent advancement in water electrolysis. The rise of hydrogen-fueled power generation and future mobility further support the development of a hydrogen economy. To address off-grid installations research gap, a hydrogen-based integrated hybrid renewable energy system (HIHRES) with a small-scale combined cycle plant is proposed. This system aims to replace aging conventional energy systems dominated by fossil fuels, which suffer from power outages and environmental issues. The paper focuses on developing a design framework for the HIHRES with a small-scale combined cycle plant for an off-grid industrial load integrated waste management facility (IWMF). The proposed configuration includes a hydrogen-based system, solar PV, combined cycle, incinerator, diesel generator, and hybrid battery-hydrogen storage. The model shows that the integrated system can provide reliable, sustainable electricity without interruption, making low-CO2 hydrogen a promising alternative. The results indicate that the hydrogen-based integrated system, coupled with primary renewables and small-scale combined cycle, addresses challenges faced by off-grid installations, such as lack of planning, difficult grid extension, technology gap and operational challenges.